IDEOLOGI PANCASILA SEBAGAI DASAR TUJUAN PEMIDANAAN DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL - Walesa Putra I Made (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Pancasila is the philosophy of the Indonesian nation and become the ideology of the state. Pancasila is also the basis of the Republic of Indonesia which largely determines Indonesia's positive legal norms. The aims of punishment has not been formulated in the national criminal law (Criminal Code / KUHP). The regulation urgency because of the basis for justifying the imposition of punishment and also determines the benefits of sanction impotion. The regulation must reflect the personality of the Indonesian nation whereas Pancasila become the National Ideology. The type of research is normative research, which is carried out based on the norms and regulations. Research results: The First, the Pancasila Ideology system which is open character has provides the opportunity for explicit regulation of the aims of punishment in positive law that follows legal developments and values in society, which retributive character (backward looking) and corrective, rehabilitative and restorative oriented (forward looking). The Second, the purpose of punishment in criminal law reform has shown conformity with the Pancasila ideology: (1) the purpose of prevention (reflecting the Principles of the 2nd Precept of Pancasila); (2) socializing convicts (based on the 5th Precepts of Pancasila); (3) conflict resolution (based on the 3rd and 4th Precepts of Pancasila); and (4) the purpose of giving sense of regret (a reflection on the first Precepts of Pancasila).